1984
DOI: 10.1016/0042-6989(84)90143-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal integration in the detection of coherent motion

Abstract: Abstract-We present data on the signal to noise threshold (SNR) for the impression of coherent. smooth motion in stroboscopicall? moving dot patterns (frame repetitionrate 100 Hz) degraded with additive noise (uncorrelated pattern each new frame). (Both patterns were 250 x 255 square arrays in which a pixel tv~ randomly assigned a light or dark value with probability SO%.) it is found that the threshold varies roughly as the inverse square root of the number of available basic dot correlation pairs. subject to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 7 publications
4
30
0
Order By: Relevance
“…Miles et al 1986), and for man in various psychophysical studies (e.g. Burr 1981;van Doom and Koenderink 1984). Particularly interesting in the present context is the study of van Doom and Koenderink (1984) which revealed that the detectability of coherent motion is gouvemed by a trade-off between the pattern size and the presentation time.…”
Section: Significance Of Spatial Integrationmentioning
confidence: 88%
See 1 more Smart Citation
“…Miles et al 1986), and for man in various psychophysical studies (e.g. Burr 1981;van Doom and Koenderink 1984). Particularly interesting in the present context is the study of van Doom and Koenderink (1984) which revealed that the detectability of coherent motion is gouvemed by a trade-off between the pattern size and the presentation time.…”
Section: Significance Of Spatial Integrationmentioning
confidence: 88%
“…Burr 1981;van Doom and Koenderink 1984). Particularly interesting in the present context is the study of van Doom and Koenderink (1984) which revealed that the detectability of coherent motion is gouvemed by a trade-off between the pattern size and the presentation time. It should be emphasized that the terms "spatial" and "temporal integration" are used here only in a colloquial and not in a mathematical sense.…”
Section: Significance Of Spatial Integrationmentioning
confidence: 99%
“…In this case, the temporal integration in Figure 4 could be exchanged for a spatial integration over detectors. Indeed van Doom and Koenderink (1983) found evidence of the interchangeability of spatial and temporal integration in motion vision. McKee and Welch (1985) have reported velocity discrimination thresholds for localized stimuli that reach asymptotic levels already at presentation times under 100 msec.…”
Section: Postcorrelation Temporal Integrationmentioning
confidence: 99%
“…A growing body ofliterature exists on the relation between time and motion, and includes such topics as velocity estimation (e.g., Algom & Cohen-Raz, 1984;Lappin, Bell, Harm, & Kottas, 1975;Tynan & Sekuler, 1982), time-of-arrival estimation (e.g., Cavallo & Laurent, 1988;Peterken, Brown, & Bowman, 1991;Schiff& Oldak, 1990), and motion detection (e.g., van Doorn & Koenderink, 1984;Verri, Girosi, & Torre, 1990). A number ofstudies have been concerned specifically with the perceived duration of moving stimuli.…”
Section: Time and Marion Studiesmentioning
confidence: 99%